The Cancer Care Monitor: psychometric content evaluation and pilot testing of a computer administered system for symptom screening and quality of life in adult cancer patients. - Fortner B; Okon T; Schwartzberg L; Tauer K; Houts AC; Fortner, Barry; Okon, Ted; Schwartzberg, Lee; Tauer, Kurt; Houts, Arthur C (Journal of Pain & Symptom Management, 2003)
Technology is making the routine screening of symptoms and the measurement of quality of life (QoL) more feasible at the point of care. However, most existing symptom screening scales and QoL measures were not developed for clinical use and were not formatted and validated for administration through computerized mediums. The Cancer Care Monitor (CCM) is a symptom-based scale developed for administration on pen-based computers. This study is an initial evaluation of the reliability and validity of the CCM. Three samples of adult outpatients provided ratings on 38 physical, psychological, and functional oriented items of the CCM that comprise six symptom scales and one global QoL index. All additive scales are converted to normalized T scores. Reliability was examined through internal consistency and confirmatory factor analysis. Convergent and divergent validity were examined by comparing CMM scores to established measures of corresponding constructs and physician judgments. Alternative forms reliability was established by comparing paper and pencil administration with computer administration. Internal consistency reliability and factor analyses confirmed the structure of the CCM as comprising six primary symptom scales and one global QoL index. Internal consistency reliabilities ranged from 0.80 to 0.89. The pattern of correlations between CCM scales and established measures supported the convergent and divergent validity of the CCM scales. Alternate forms reliability based on paper and computer forms of the CCM scales was high. Patients indicated a preference for the computer-administered version. Results suggest that CCM items can be scored as a reliable and valid measure of constructs related to physical, psychological, and functional status, and global health-related QoL in adult cancer patients. Future studies should replicate and further evaluate the properties of the CCM, especially in relation to clinical utility.